Influence of oral aesthetics on overall appraisal of facial aesthetics - S. Abirami; Shaista Afroz; Tabassum Nawab; Geeta Rajput (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Uneven dentition is a cause of dissatisfaction to many. However, irregularities in teeth may be less unattractive when viewed from a full-face perspective than from a circumoral view. Purpose: To ascertain the influence of dental aesthetics (DA) on the overall appraisal of facial aesthetics (FA) and to compare the perception of the general population with that of dental experts. Methods: Frontal and circumoral view photographs with mild-to-moderate dental asymmetries were selected for FA and DA evaluation. Participants from the general population assessed attractiveness using a questionnaire (validated in a pilot study) with questions on FA and DA. Dental experts assessed attractiveness using the Dental Esthetic Screening Index with extraoral and intraoral components. Smile mesh measurements were taken to calculate the various attributes of smiles. Results: The experts considered that all the images had insufficient-to-good aesthetics (mean score: 20.82±6.545), and a statistically significant correlation was identified between the two variables (R2=0.04, p=0.0015). The general population considered all the images to have satisfactory-to-good aesthetics (mean score: 15.8±3.006), and no correlation was identified between the two variables for all the images taken individually and cumulatively (R2=0.002, p=0.46). It was observed that there was a statistically significant correlation between patient scores as the dependent variable and expert scores as the independent variable (R2=0.24, p<0.001). Conclusion: Facial attractiveness overshadowed dental irregularities and influenced the general population’s judgment; however, the dental experts’ judgment was influenced by intraoral aesthetics.